Recent Advances in Natural Products Derived from Marine Echinoderms and Endophytic Microbes: Chemical Insights and Therapeutic Potential - Shuangyu Li; Yan Xiao; Qiang Li; Mingzhi Su; Yuewei Guo; Xin Jin (Marine Drugs)
Echinoderms, a diverse group of marine invertebrates including starfish, sea urchins, and sea cucumbers, have been recognized as prolific sources of structurally diverse natural products. In the past five years, remarkable progress has been made in the isolation, structural elucidation, and pharmacological assessment of these bioactive compounds. These metabolites, including polysaccharides, triterpenoids, steroids, and peptides, demonstrate potent bioactivities such as anticancer, anti-inflammatory, antiviral, and antimicrobial effects, providing valuable insights and scaffolds for drug discovery. This review highlights the structural diversity and biological activities of natural products derived from echinoderms over the last five years, with a particular focus on their structure–activity relationships and therapeutic potential. It also outlines the prospects and challenges for future research, aiming to stimulate further exploration in marine drug discovery.